Prácticas lectoras tradicionales de los acompañantes pedagógicos - Rivas Plata Álvarez, María del Rosario (2015)
This research delved into the theme of thetrend and motivation for reading of thebudget accompanying educational programfocusing on results “Learning achievementsof students in regular basic education” -PELA.